Cross-cultural similarities and differences in reporting autistic symptoms in toddlers: A study synthesizing M-CHAT(-R) data from ten countries. (July 2022) - Stevanovic, Dejan; Robins, Diana L.; Costanzo, Floriana; Fucà, Elisa; Valeri, Giovanni; Vicari, Stefano; Erkuran, Handan Ozek; Yaylaci, Ferhat; Albores-Gallo, Lilia; Gatica-Bahamonde, Gabriel; Gabunia, Maia; Zirakashvili, Medea; et al.
Abstract: Background: This study aimed to evaluate the endorsement rates of M-CHAT(-R) items by parents/caregivers of toddlers with autism spectrum disorder (ASD) synthesizing data from ten countries: Albania, Chile, Georgia, Macedonia, Malaysia, Mexico, Serbia, Turkey, United Kingdom, and the United States of America. Method: Data were aggregated for toddlers aged 14–36 months who participated in previous studies or completed clinical screening. An item with < 30% of endorsements was classified as low endorsement, an item falling within the range of 30–60% as moderate endorsement, and an item with > 60% as high endorsement. Results: All items had a low endorsement rate in at least one country and moderate to high in others. Of 20 items, 14 had a moderate to high endorsement rate in seven to nine countries. Of particular relevance are items with moderate to high endorsement rates in all countries excluding Malaysia, such as points to get help, points to show, brings things to show, follows a point, follows your gaze, and understands what is said. On the other hand, makes eye contact, responds to name, hearing concerns, and reciprocal smile were interpreted differently across the countries. Conclusions: This study showed differences in parent/caregiver responding to M-CHAT(-R) items across ten countries, which may indicate cross-country variations in the recognition and evaluation of autistic symptoms in toddlers. Items related to joint attention, social engagement, and language comprehension were reported in a similar manner across countries and could be interpreted as universal autistic symptoms in toddlers. Highlights: Cross-country variations exist in reporting autistic symptoms with the M-CHAT(-R). Joint attention and engagement more likely interpreted universally as atypical. ASD screening with the M-CHAT(-R) needs to consider culturally sensitive aspects.